PERAN MODERASI DAN MEDIASI PERILAKU INOVASI: HUBUNGAN ANTARA KEPEMIMPINAN AMBIDEXTROUS, BUDAYA ORGANISASI DAN IKLIM INOVASI ORGANISASI - Khan, Ryan Basith Fasih; Mardliyah, Imayatin; Salsabila, Aqila; Fitriah, Aida (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2025)
This study aims to explain how ambidextrous leadership affects innovative behaviour, organisational innovation climate, and organisational culture at workplace environment on employees. A survey of 167 employees in Malang, East Java was carried out to understand this phenomenon. This study uses quantitative approach, and data were collected from employees in the services industry by using partial least square method. The results show that ambidextrous leadership, which involves idea development and realisation simultaneously, significantly affects employees’ innovative behaviour. Ambidextrous leadership effectively allows employees to develop new ideas and encourages them to be more innovative and to contribute to the competitiveness of the organisation more sustainably in the long term. Organisational culture does not have a significant moderating effect. The mediating effects of organisational innovation climate, ambidextrous leadership transmission on innovative behaviour are found, and have an indirect effect through their ability to improve organisational innovation climate. Keywords: ambidextrous leadership; organisational culture; organisational innovation climate; innovation behaviour. Penelitian ini menjelaskan bagaimana ambidextrous leadership memengaruhi perilaku inovasi, iklim inovasi organisasi, dan budaya organisasi di lingkungan kerja bagi karyawan. Penelitian ini dilakukan dengan menyurvei 167 karyawan di Malang, Jawa Timur, Indonesia, untuk memahami fenomena ini. Penelitian ini menggunakan desain penelitian kuantitatif, data survei yang dikumpulkan dari karyawan di industri jasa, dan pendekatan metode partial least square. Hasilnya, ambidextrous leadership, yang melibatkan pengembangan ide dan realisasi ide secara bersamaan, berdampak signifikan pada perilaku inovatif karyawan. Model kepemimpinan ambidextrous leadership secara efektif memberi karyawan ruang untuk mengembangkan ide-ide baru, yang mendorong karyawan untuk terlibat dalam perilaku yang lebih inovatif dan berkontribusi positif terhadap kemajuan dan daya saing organisasi dalam jangka panjang dan keberlanjutan. Peran moderasi budaya organisasi tidak secara signifikan memengaruhi variabel yang diteliti dan perilaku inovasi. Peran mediasi iklim inovasi organisasi, transmisi ambidextrous leadership pada perilaku inovatif karyawan dan berdampak secara tidak langsung melalui kemampuannya untuk menumbuhkan iklim organisasi yang inovatif. Kata kunci: ambidextrous leadership; budaya organisasi; iklim inovasi organisasi; perilaku inovasi.